Psychological and cognitive effects of laser printer emissions: A controlled exposure study. (28th October 2017) - Herbig, B.; Jörres, R. A.; Schierl, R.; Simon, M.; Langner, J.; Seeger, S.; Nowak, D.; Karrasch, S.
Abstract: The possible impact of ultrafine particles from laser printers on human health is controversially discussed although there are persons reporting substantial symptoms in relation to these emissions. A randomized, single‐blinded, cross‐over experimental design with two exposure conditions (high‐level and low‐level exposure) was conducted with 23 healthy subjects, 14 subjects with mild asthma, and 15 persons reporting symptoms associated with laser printer emissions. To separate physiological and psychological effects, a secondary physiologically based categorization of susceptibility to particle effects was used. In line with results from physiological and biochemical assessments, we found no coherent, differential, or clinically relevant effects of different exposure conditions on subjective complaints and cognitive performance in terms of attention, short‐term memory, and psychomotor performance. However, results regarding the psychological characteristics of participants and their situational perception confirm differences between the participants groups: Subjects reporting symptoms associated with laser printer emissions showed a higher psychological susceptibility for adverse reactions in line with previous results on persons with multiple chemical sensitivity or idiopathic environmental intolerance. In conclusion, acute psychological and cognitive effects of laser printer emissions were small and could be attributed only to different participant groups but not to differences in exposure conditions in terms of particle number concentrations.